Device profile of the AltaValve system for transcatheter mitral valve replacement: overview of its safety and efficacy. (2nd July 2020) - Alperi, Alberto; del Val, David; Ferreira-Neto, Alfredo Nunes; Bernier, Mathieu; B Freitas-Ferraz, Afonso; Dagenais, François; Rodés-Cabau, Josep
ABSTRACT: Introduction: In patients with severe mitral regurgitation (MR), transcatheter mitral valve replacement (TMVR) has recently emerged as an alternative to surgery. However, compared with transcatheter aortic valve replacement, TMVR faces several technical challenges and a high screening failure rate, mainly due to a more complex mitral annulus geometry and the potential interaction with the sub-valvular apparatus and the left ventricular outflow tract (LVOT). The AltaValve system is a device intended for TMVR with unique design features that may overcome most anatomical limitations for this therapy. Areas covered: A summary of the current evidence regarding TMVR is presented, followed by a review of the main technical challenges. The main features, differential characteristics, and potential advantages of the AltaValve system are discussed. Finally, we describe the first-in-human procedures with AltaValve and the main details of the upcoming feasibility trial. Expert opinion: A high number of high-risk surgical patients with MR remain undertreated. TMVR is continuously evolving, and AltaValve constitutes another step forward in this field. Its unique design avoiding annular and LVOT engagement represents a clear potential benefit, along with its recently incorporated trans-septal approach system. However, more evidence is warranted regarding its feasibility in different clinical settings and mid-term performance.